Evaluasi Penyelesaian Temuan Pemeriksaan yang Tidak Dapat Ditindaklanjuti (TPTD) Hasil Pemeriksaan Inspektorat Jenderal - Sari, Wulan; S, Dwi Setiawan (Owner : Riset dan Jurnal Akuntansi, 2024)
This study aims to evaluate the implementation of the TPTD settlement process from the Inspectorate General examination results compared to the applicable TPTD guidelines. The study was conducted at the Inspectorate General of the Ministry of Health. This research uses a case study research strategy with a qualitative descriptive data analysis method. The data sources used were obtained from interviews and documentation. The results showed that the implementation of the settlement has followed the applicable TPTD guidelines but it is necessary to update the follow-up guidelines and make technical follow-up instructions for the results of supervision or TPTD special guidelines that explain the operational definition of TPTD criteria regarding benchmarks and document limits from authorized agencies that must be met as TPTD requirements, work steps regarding the TPTD proposal mechanism from the work unit, discussion and determination of TPTD by the Inspectorate General, as well as the format of submitting TPTD proposals along with supporting data that must be completed. Recommendations of audit results that become TPTD due to improper provision of recommendations The Inspectorate General can carry out the development of APIP competence of the Inspectorate General on an ongoing basis. The findings decided by TPTD but seen from the follow-up carried out are not timely or protracted, it is necessary to monitor the follow-up carried out by the Inspectorate General every month and be actively involved in maintaining the time commitment. Keywords: Findings, follow-up Inspectorate General, TPTD, recommendations